Manifestation of the batang banyu concept as a community communication experience - Fahrianoor (Jurnal Studi Komunikasi, 2023)
The existence of a unique concept of a river has significantly shaped the Banjarese community's relationship with it. This unique perspective, known as "Batang Banyu," portrays the river as a revered and integral aspect of their existence. The core objective of this research lies in comprehending the embodiment of the Batang Banyu concept within the regions of Martapura, Nagara, and Panggang in South Kalimantan. The research adopts a phenomenological approach, utilising an interpretive qualitative method to achieve this. The primary data is gathered through rigorous field observations and in-depth interviews with local inhabitants. The study's outcomes unveil that the Batang Banyu concept has evolved into a communicative experience, endowing the community with profound significance for the river. This significance finds manifestation in four fundamental aspects: first and foremost, the river serves as a livelihood for fishermen; secondly, it supports various livelihood-related endeavours; thirdly, it plays a crucial role in constructing homes; and lastly, it serves as a means of transportation. Remarkably, among the communities residing along the banks of the Nagara River and Panggang Lake, the Batang Banyu concept remains firmly entrenched. Conversely, for the people residing along the Martapura River, the Batang Banyu concept has been discarded, resulting in the unfortunate neglect and pollution of the Martapura River due to the accumulation of vast amounts of garbage.